(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
Extensive Reading (ER) programs, which encourage students to read large amounts of material at their own level and pace, have become an increasingly popular tool in language education. This article explores the impact of ER on the four core language skills—listening, speaking, reading, and writing—and provides insights into implementing successful ER programs.